2017
DOI: 10.1161/circinterventions.116.004497
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Double Kissing Crush Versus Provisional Stenting of Coronary Artery Bifurcation Lesions

Abstract: Background—Provisional stenting is effective for anatomic simple bifurcation lesions. Double kissing crush stenting reduces the 1-year rate of target lesion revascularization. This study aimed to investigate the 5-year clinical results of the DKCRUSH-II study (Randomized Study on Double Kissing Crush Technique Versus Provisional Stenting Technique for Coronary Artery Bifurcation Lesions).Methods and Results—A total of 370 patients with coronary bifurcation lesions who were randomly assigned to either the doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 22 publications
(43 reference statements)
2
49
0
Order By: Relevance
“…Interestingly, this study demonstrated that the risk of cardiac death that reached a statistical difference was limited to trials with a follow-up duration ≤6 months. However, there were no significant difference in cardiac death between both difference strategies when the follow-up duration was extended to more than 6 months, which also was similar to the study of Chen et al [30] (2.2% vs. 3.3%, P = .513). Among the different studies included in this meta-analysis, only trial of Chen et al demonstrated that there was no significant difference in late-term cardiac death between the 2 stenting and provisional stenting strategies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, this study demonstrated that the risk of cardiac death that reached a statistical difference was limited to trials with a follow-up duration ≤6 months. However, there were no significant difference in cardiac death between both difference strategies when the follow-up duration was extended to more than 6 months, which also was similar to the study of Chen et al [30] (2.2% vs. 3.3%, P = .513). Among the different studies included in this meta-analysis, only trial of Chen et al demonstrated that there was no significant difference in late-term cardiac death between the 2 stenting and provisional stenting strategies.…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that there was no significant difference in stent thrombosis between both strategies. Similar to this study, Chen et al [30] and Maeng et al [31] also reported no significant difference in long-term stent thrombosis (0% vs. 1.1%, 1.5% vs. 3%) between conventional stenting (crush and culotte) and provisional stenting during the follow-up of 5 years. The standard of dual antiplatelet therapy after PCI is 12 months at least; discontinuous antiplatelet therapy may be the important reason for stent thrombosis event.…”
Section: Discussionsupporting
confidence: 86%
“…When performing meta regression for acute coronary syndrome (ACS) patients, provisional stenting actually reported harm. This was confirmed in the DK Crush II trial 22 …”
Section: Discussionmentioning
confidence: 55%
“…Both DK crush and Mini‐crush techniques involve stenting the side branch initially. This is done to protect from abrupt occlusion and is likely beneficial in severe SB disease 7‐9,21‐23 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some of the best clinical results have been obtained from the double kissing strategy of the DK-crush technique. [25][26][27] Figure 5 illustrates the principle of incorporating POT during two-stent bifurcation procedures. The first POT is performed after the first stent has been implanted, to appose the stent in the proximal main vessel and open the struts to facilitate optimal guidewire re-crossing.…”
Section: Implications For a 2-stent Strategymentioning
confidence: 99%